2019
DOI: 10.1111/wej.12510
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of farmers' time perspective in water resources exploitation behaviour in the eastern area of Lake Urmia, Iran: An environmental psychological analysis

Abstract: This study aimed to analyse the mediating role of farmers' time perspective in water resources exploitation behaviour/s (WREB). The study was descriptive correlational and causal relational and was carried out using a survey. The statistical population consisted of farmers in the eastern area of Lake Urmia (N = 232 295), of whom 386 persons were selected using a stratified random sampling method. The instrument was a questionnaire, whose validity was confirmed by a panel of experts. Its reliability was also ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…An answer to this question may shed light on the question of whether or not the lake can be sustainably restored. In the Urmia lake basin, numerous studies have been conducted on the behavior of humans regarding water consumption (Anbari et al, 2021;Mahdavi, 2021;Pouladi et al, 2019Pouladi et al, , 2021Sadeghi et al, 2020;Shojaei-Miandoragh et al, 2020). The purpose of these studies was to identify human factors contributing to Lake Urmia's dryness and to suggest solutions to resolve the problem.…”
Section: Introductionmentioning
confidence: 99%
“…An answer to this question may shed light on the question of whether or not the lake can be sustainably restored. In the Urmia lake basin, numerous studies have been conducted on the behavior of humans regarding water consumption (Anbari et al, 2021;Mahdavi, 2021;Pouladi et al, 2019Pouladi et al, , 2021Sadeghi et al, 2020;Shojaei-Miandoragh et al, 2020). The purpose of these studies was to identify human factors contributing to Lake Urmia's dryness and to suggest solutions to resolve the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable agriculture relies on farmers' knowledge, attitude, skill, and management (Ahnstrom et al, 2009;Abu Samah et al, 2012;Sadeghi et al, 2020). Lambrechts et al (2013) argue that to apply sustainability principles and tackle sustainability challenges, one needs sustainability knowledge, skills, values, and attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, conducting social and behavioural inquiries to ensure environmental stability and improve human living environments is vital and very important (Fallah Haghighi et al, 2018; Sabzali Parikhani et al, 2018; Vlek & Steg, 2007). The social and psychological characteristics of farmers are key to agricultural change, and researches have shown that their attitudes towards the natural environment led to the formation of their environmental behaviours and the acceptance of environmental protection measures (Sadeghi et al, 2020; Shojaei‐Miandoragh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%